Documenting and disseminating agricultural indigenous knowledge for sustainable food security: the efforts of agricultural research libraries in Nigeria (2014)
Developing the agricultural sector remains a critical factor towards the achievement of sustainable food production and, indeed, global food security. While indigenous agricultural knowledge is of immense value in improving food production, its documentation and dissemination remain a big challenge confronting librarians and other information professionals, particularly in Africa where traditional practices are prevalent. This study, therefore, investigated the efforts of agricultural research libraries in Nigeria in documenting and disseminating agricultural indigenous knowledge towards achieving sustainable food security in the country. It also determined the agricultural indigenous practices that have been documented as well as the obstacles to the documentation of agricultural indigenous knowledge. Librarians in selected agricultural research libraries in Nigeria constituted the target population of the study, and a questionnaire was the instrument used for data collection. Based on the findings of the study, recommendations have been made aimed at improving the documentation and dissemination of agricultural indigenous knowledge in order to enhance food security in Nigeria.